OPTIMALISASI MANAJEMEN SAMPAH DI KOTA BIMA DALAM MEWUJUDKAN LINGKUNGAN YANG BERSIH DAN SEHAT - Zulharman Zulharman; Mustafa Mustafa; Ramdan Yusuf; Tamrin Fathoni; Achmad Abdul Azis (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2023)
Bima City in Creating a Clean and Healthy Environment. In implementing this service, the ABCD (Asset-Based Community Development) method is the main basis that prioritizes the potential and assets that exist in the community as a starting point for developing a sustainable waste management program. The approach applied is participatory, enabling collaboration between communities, local governments, and other stakeholders in identifying relevant problems and assets related to waste management. Various data collection techniques were used, including interviews, surveys, observations, and focus group discussions, with the main data sources coming from the local community, local government, and related literature references. This approach aims to explore the potential that exists in society and encourage active participation in formulating sustainable solutions related to waste. The research results show that optimizing waste management in Bima City, NTB, requires integrated efforts, including separate waste collection, education, and strict regulations. Implementation of these efforts can produce a cleaner and healthier environment, increase income and environmental awareness, and maintain a balance between current and future needs